2023
DOI: 10.1002/jbm.b.35345
|View full text |Cite
|
Sign up to set email alerts
|

Local delivery of adeno‐associated viral vectors with electrospun gelatin nanofiber mats

Kotoko Furuno,
Kelum Chamara Manoj Lakmal Elvitigala,
Keiichiro Suzuki
et al.

Abstract: Adeno‐associated viral (AAV) vectors play a significant role in gene therapy, yet the typical delivery methods, like systemic and local AAV injections, often lead to unintended off‐target distribution and tissue damage due to injection. In this study, we propose a localized delivery approach for AAV vectors utilizing electrospun gelatin nanofiber mats, which are cross‐linked with glutaraldehyde. The AAV vectors, which encoded a green fluorescent protein (GFP), were loaded onto the mats by immersing them in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…We reported a similar result for electrospun gelatin fabrics applied to mouse liver [23]. As reported in various studies, electrospun fibers have been shown to be effective for the local delivery of vectors [16,[21][22][23]30]. However, it is impossible to completely prevent their off-target distribution, and not only with PDO fibers, due to the diffusion of the released vectors through the bloodstream and body fluids.…”
Section: In Vivo Transduction and Genome Editingsupporting
confidence: 81%
See 2 more Smart Citations
“…We reported a similar result for electrospun gelatin fabrics applied to mouse liver [23]. As reported in various studies, electrospun fibers have been shown to be effective for the local delivery of vectors [16,[21][22][23]30]. However, it is impossible to completely prevent their off-target distribution, and not only with PDO fibers, due to the diffusion of the released vectors through the bloodstream and body fluids.…”
Section: In Vivo Transduction and Genome Editingsupporting
confidence: 81%
“…The large surface areas of the fabrics allow for the efficient loading and retention of genes, and the utility of electrospun nonwoven fabrics as a substrate for gene delivery has been demonstrated [16,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation